Study of environmental thermal variation in vineyards harvested by different curtain colors used as lateral closure - Ávalo, Helio; Santos, Rodrigo Couto; Cereda, Marney Pascoli; Morais, Glaucia Almeida de (Interações, 2019)
The objective of this research was to evaluate the thermal influence of the white and blue colors of the sanitary curtain used as lateral closures in commercial broiler chickens, aiming at the welfare and environment suitable for the production of broilers. At the end of 42 days, the white curtain represented the best average surface temperature, between 27.4º and 35.5º, when evaluated without supplementary ventilation. It was also possible to conclude that the white color curtain was more efficient to maintain the well-being inside the aviary, especially in the sixth week of production, verified by infrared thermography.